THE CONTRIBUTION OF DR (HC) H. MUSTAFA MUHAMMAD NURI, LAS IN DEVELOPING ARABIC LEARNING IN SOUTH SULAWESI - Muthalib, Abdul; Ilyas, Hamka; Haniah, Haniah (Jurnal Diskursus Islam, 2022)
This study discusses the contribution of Dr. (HC) H. Mustafa Muhammad Nuri, LAS, in the Development of Arabic Learning in South Sulawesi to know the teaching model from Dr. (HC) H. Mustafa Muhammad Nuri, LAS, in Arabic learning in South Sulawesi. This type of research was a qualitative descriptive located in South Sulawesi using a historical, sociological, and psychological approach. The data collection techniques used were interviews and documentation. In addition, this research also used library research through primary and secondary data. The data analysis techniques were in-depth by reducing data, presenting data, and drawing conclusions. The results showed that Dr. (HC) H. Mustafa Muhammad Nuri, LAS has an essential role in developing Arabic learning in South Sulawesi by contributing as Dean of the Faculty of Adab and Humanities at IAIN Alauddin Makassar (1968-1985) and in (1990-1997). He is the Director and lecturer at the Language Institute and the Author of Arabic books and wall magazines. Besides, he teaches Arabic learning at home, is an initiator of the collaboration between IAIN Alauddin Makassar and the Middle East, an authoritative source, the educators who educate and foster Arabic teachers and lecturers, and a pioneer of the eclectic method.